ANALYSIS OF LABOR REMUNARATION POLICY IN THE EDUCATION SECTOR FROM THE POINT OF VIEW THE DECLINE LABOR CONCEPT (INNOVATIVE ECONOMY, 2020)
Tsymbaliuk S.O. ANALYSIS OF LABOR REMUNARATION POLICY IN THE EDUCATION SECTOR FROM THE POINT OF VIEW THE DECLINE LABOR CONCEPT Purpose. The purpose of the study is to substantiate theoretical and methodological principles that reveal the essence of the concept “decent labour remuneration”, the development of indicators for estimating the remunaration policy from the point of view of the implementation of principles of decent work at the sectoral level and the analysis of the policy of remuneration in the education sector using the developed indicators and standards.Methodology of research. In the course of the research general scientific and special methods of research were used, in particular: economical and statistical methods, comparative analysis, analogue method, content analysis – when formulating of conceptual foundations that reveals the essence of the notion of "decent labour remuneration" and when determining the basic parameters of wages, as well as the analysis of the labour remuneration policy on the basis of the developed indicators.Findings. Issues of labour remuneration play a key role in theory and practice of the decent work conception. Decent labour remuneration is an essential component of the decent work conception. The reward received by an employee plays a central role in creating good conditions for the reproduction of his (her) labour, the professional development and the creation of decent living conditions. The conceptual provisions that reveal the essence of the concept “decent labour remuneration” have been formulated. The policy of labour remuneration from the point of view of implementation of principles of decent work in the education sector in Ukraine has been analyzed. The analysis has shown negative trends, in particular low level of wages, insufficient structure and differentiation of remunaration, low level of collective-contractual regulation of remuneration in the education sector. The current policy of labour remuneration leads to devaluation of the prestige of pedagogical and scientific activities, loss of human capital in the education, deepening of social inequality. The necessity of improvement of organizational and economic mechanism for determining the basic parameters of remuneration in order to implementation of decent labour remuneration has been proved. The determination of the basic parameters of remuneration must be based on the usage of market and contractual elements for regulation of the level and structure of remuneration, as well as the implementation of innovative approaches and tools for the formation of various components of rewards.Originality. Indicators and standards for estimating remuneration policy in relation to implementation of principles of decent work at the sectoral level have been worked out.Practical value. Developed indicators and standards for estimating remuneration policy at the sectoral level can be used by ministries, trade union organizations, employers’ organizations for analyzing remuneration policy and identifying directions for improvement in order to implement of the decent work concept.Key words: labour remuneration; labour remuneration policy; decent work decent labour remuneration; indicators for estimating remuneration policy.
Keywords: Key words; labour remuneration; labour remuneration policy; decent work decent labour remuneration; indicators for estimating remuneration policy.